PARADOXES, PARABLES AND CONUNDRUMS: A NEW SENSE OF COMMUNITY? - Bishop, Brian; Vicary, D. (2003)
Research into the psychological sense of community has been characterized as largely being based on an idealized form of community (Dunham, 1986). Community has been seen in terms of functionalist perspective with few researchers looking at the conflicts and ension of community living. There has been little critical analysis of what community is and what our sense of it is. A series of parables, paradoxes and conundrums are presented to raise the questions of what we are dealing with when we look at people's psychological sense of community. We speculate, even pontificate, about the some of the issues that we suggest may help in a more critical examination of the concept and role of sense of community.